2019
DOI: 10.1002/nafm.10371
|View full text |Cite
|
Sign up to set email alerts
|

We Ain't Afraid of No Ghosts: Tracking Habitat Interactions and Movement Dynamics of Ghost Tags under Differing Flow Conditions in a Sand‐Bed River

Abstract: The use of PIT tags has rapidly proliferated since their introduction, and new mobile detection methods have been developed. However, the presence of ghost tags (i.e., PIT tags left in the system after a fish dies) creates uncertainty about the status (live or dead) of tags detected. Herein, we describe our raft‐based mobile PIT tag antenna system, which was used to evaluate the movements of “seeded tags” (i.e., PIT tags that we placed in the river as ghost tag analogs) and their interactions with habitat feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…We expected differences in movement between ghost tags and live fish would be important in classification. Razorback sucker, flannelmouth sucker, and Colorado pikeminnow are all known to move very large distances (McKinney et al 1999;Irving and Modde 2000;Zelasko et al 2010), and while ghost tags can move distances up to 4 km (Bond et al 2019;Stout et al 2019), we observed a large difference between the two classes. Fish carcasses can also move large distances after death (Havn et al 2017), but the average time for a white sucker carcass to shed an abdominally located tag was only 73.3 h (Muhametsafina et al 2014).…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…We expected differences in movement between ghost tags and live fish would be important in classification. Razorback sucker, flannelmouth sucker, and Colorado pikeminnow are all known to move very large distances (McKinney et al 1999;Irving and Modde 2000;Zelasko et al 2010), and while ghost tags can move distances up to 4 km (Bond et al 2019;Stout et al 2019), we observed a large difference between the two classes. Fish carcasses can also move large distances after death (Havn et al 2017), but the average time for a white sucker carcass to shed an abdominally located tag was only 73.3 h (Muhametsafina et al 2014).…”
Section: Discussionmentioning
confidence: 49%
“…As expected, live fish generally moved greater distances than the ghost tags. Also, fish and other organisms exhibit behavioral changes to minimize the effect of high flows (Lytle and Poff 2004), and ghost tags respond to higher flows similarly to sediment (Bond et al 2019;Stout et al 2019). Therefore, we expected ghost tags and live fish to exhibit different responses to changes in discharge, and this expectation was demonstrated by the fifth variable influencing classification, monsoonal flows.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations